Control of Heat Capacity of Moisture Sensor by Galvanic Arrays with Micro/Nano Gap. (8th September 2020) - Kubota, Yusuke; Satoh, Norifusa; Sakamoto, Yukihiro; Kawakita, Jin
Abstract : Occurrence of dew condensation depends on the surface temperature of the target. In order to adjust the temperature of the senor surface to that of the target, the temperature changing rate of the sensor surface was controlled by simply attaching heat sink to the backside of the sensor chip and by introducing thermal insulation around the backside of the sensor chip in this study. Experimental results demonstrated that the temperature change of the sensor surface was successfully relaxed against that of environment around the sensor surface and that the galvanic arrays with the micro/nano gaps on the sensor chip detected occurrence of dew condensation even under 100% in the relative humidity of environment. It is expected that the surface status of this sensor could be made closer to the target on application such as dew condensation detection.